Performance evaluation of clinical diagnostic kits for Group B Streptococcus available in China - Rong Su; Xiaoli Chen; Shouneng Lu; Yujie Zhou; Yue Liu; Qiongzi Huang; Ying Zhang; Xinyan Zheng; Mengting Li; Wangheng Hou; Kunyu Yang; Huiming Ye; et al. (Microbiology Spectrum, 2026)
ABSTRACT Group B Streptococcus (GBS) is a significant pathogen capable of causing postpartum bacteremia in pregnant women and vertical transmission to neonates, which can result in fatal outcomes. Therefore, prenatal screening for vaginal GBS colonization is essential for preventing neonatal transmission. This study conducted an external quality assessment to evaluate the performance of 12 commercially available GBS detection kits in China. A total of 12 GBS detection kits (three antigen-based and nine nucleic acid-based) were evaluated using a reference panel comprising 11 GBS serotypes. The limit of detection (LOD) and repeatability were assessed for the antigen kits, and the LOD was determined for the nucleic acid detection kits. Nucleic acid testing achieved higher sensitivity than antigen-based methods. Antigen detection kits exhibited sensitivities ranging from 10⁴ to 10⁷ colony-forming units (CFU)/mL, with repeatability of at least 95%. Nucleic acid detection kits demonstrated sensitivities ranging from 10² to 10⁵ CFU/mL. Notably, certain kits showed reduced detection efficiency for serotypes Ia, III, VIII, and IV. The diagnostic performance of antigen detection kits and nucleic acid detection kits for detecting different serotypes varied. These findings underscore the potential for serotype-related analytical bias in clinical practice and emphasize the necessity of comprehensive kit validation. IMPORTANCE Group B Streptococcus (GBS) is a leading cause of severe infections in newborns, often transmitted from colonized mothers during childbirth. Accurate prenatal screening is therefore critical. In China, numerous rapid test kits are used for GBS detection, but whether they perform equally well across different bacterial types (serotypes) was unknown. Our study systematically evaluated 12 commercially available kits and found that some fail to reliably detect certain high-risk serotypes, including one strongly linked to fatal newborn infections. These findings underscore the potential for serotype-related analytical bias in clinical practice and emphasize the necessity of comprehensive kit validation, thereby supporting more accurate screening to protect maternal and neonatal health.